2019
DOI: 10.1186/s12957-019-1628-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of robotic gastrectomy and laparoscopic gastrectomy for gastric cancer in terms of their long-term oncological outcomes: a meta-analysis of 3410 gastric cancer patients

Abstract: Background Data regarding the long-term oncological outcomes of robotic gastrectomy (RG) are limited despite the increased commonality of this method as an alternative for gastric cancer treatment. Here, we conducted a meta-analysis to evaluate the long-term oncological outcomes of RG in comparison to that of laparoscopic gastrectomy (LG). Methods The PubMed, ISI Web of Science, EMBASE, and Cochrane Library databases were comprehensively searched for studies that compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
4
14
0
1
Order By: Relevance
“…Because gastric cancer is a malignant tumor,the long-term follow-up oncological outcomes of gastric cancer patients were major concerns of surgeons.OS is a major oncologic outcome.In this meta analysis, the OS was similar to that previously reported [54].The pooled data of the included studies revealed no signi cant difference between the RG and LG groups in OS, RFS, and the recurrence rate without heterogeneity. These results show that the two techniques have similar long-term oncologic outcomes.As far as we know,few metaanalysis had previously reported RFS with RG and LG.The RFS and recurrence rate results further demonstrated the comparability between RG and LG as far as long-term oncological outcomes in this meta analysis.…”
Section: Discussionsupporting
confidence: 86%
“…Because gastric cancer is a malignant tumor,the long-term follow-up oncological outcomes of gastric cancer patients were major concerns of surgeons.OS is a major oncologic outcome.In this meta analysis, the OS was similar to that previously reported [54].The pooled data of the included studies revealed no signi cant difference between the RG and LG groups in OS, RFS, and the recurrence rate without heterogeneity. These results show that the two techniques have similar long-term oncologic outcomes.As far as we know,few metaanalysis had previously reported RFS with RG and LG.The RFS and recurrence rate results further demonstrated the comparability between RG and LG as far as long-term oncological outcomes in this meta analysis.…”
Section: Discussionsupporting
confidence: 86%
“…OS is a major oncologic outcome. In this meta-analysis, the OS was similar to that previously reported [58]. The pooled data of the included studies revealed no significant difference between the RG and LG groups in OS, RFS, and the recurrence rate without heterogeneity.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, regarding the long-term results, the majority of the literature compared robot-assisted surgery and laparoscopy, without differences in terms of disease-free and overall survival [41][42][43]. In our series, as shown by other studies comparing robotic and open gastrectomy, no significant differences were observed in terms of OS and DFS between the two surgical approaches [44].…”
Section: Discussionsupporting
confidence: 49%